2017
DOI: 10.1098/rspb.2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

Joint histology inAlligator mississippiensischallenges the identification of synovial joints in fossil archosaurs and inferences of cranial kinesis

Abstract: Archosaurs, like all vertebrates, have different types of joints that allow or restrict cranial kinesis, such as synovial joints and fibrous joints. In general, synovial joints are more kinetic than fibrous joints, because the former possess a fluid-filled cavity and articular cartilage that facilitate movement. Even though there is a considerable lack of data on the microstructure and the structure-function relationships in the joints of extant archosaurs, many functional inferences of cranial kinesis in foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Sections of the otic joint revealed a unichondral joint in which the hylaline cartilage-capped epiphysis of the otic process of the quadrate abuts layers of fibrous connective tissue surrounding the paraoccipital process and squamosal. This morphology is also similar to that found in the otic joint of gecko (Payne et al, 2011) and alligator (Bailleul and Holliday, 2017).…”
Section: Histologysupporting
confidence: 85%
See 1 more Smart Citation
“…Sections of the otic joint revealed a unichondral joint in which the hylaline cartilage-capped epiphysis of the otic process of the quadrate abuts layers of fibrous connective tissue surrounding the paraoccipital process and squamosal. This morphology is also similar to that found in the otic joint of gecko (Payne et al, 2011) and alligator (Bailleul and Holliday, 2017).…”
Section: Histologysupporting
confidence: 85%
“…Our results also support the findings of Mezzasalma et al (2014) that the histology of the joint may not necessarily be as important as the morphology for kinesis, as the soft tissue joint models (JL2-4) revealed similar patterns of strain and deformation. Furthermore, Bailleul et al (2016) and Bailleul and Holliday (2017) found gross bony morphology does not always reflect the types of connective tissues in archosaur skulls. Moreover, cranial joint tissues may behave considerably differently in dynamic, rather than static loading conditions.…”
Section: Discussionmentioning
confidence: 96%
“…As explained above, a fibrous‐based contact is indicative of a syndesmosis, which allows for limited mobility (Barnett et al ; Kardong, ). The presence of calcified cartilage, more distally along the margins of the sacral ribs, interposed between the subchondral bone and the fibres, suggests that this contact transitions to a synchondrosis towards the ISJ, similarly to what is described by Bailleul & Holliday () for some cranial joints of modern alligators.…”
Section: Discussionsupporting
confidence: 65%
“…The hypothesis that physical movement may be responsible for secondary cartilage formation has been previously proposed for some cranial joints in both birds and mammals (Murray, 1963; Murray & Drachman, 1969; Bareggi et al, 1994), but the degree and/or direction of such movement has not been quantified. Nevertheless, cranial tissues have great potential for more accurate inferences regarding skull structure and function (e.g., cranial kinesis or akinesis) in non-avian dinosaurs and other fossil archosaurs (e.g., see Bailleul & Holliday, 2017; Lessner et al, 2019).…”
Section: Xxist Century Trends: Skull Histologymentioning
confidence: 99%